Gastric trichobezoar in an end-stage renal failure and mental health disorder presented with chronic epigastric pain: A case report - Aishath Azna Ali; Rajan Gurung; Zeena Mohamed Fuad; Muaz Moosa; Isha Ali; Ahmad Abdulla; Assikin Muhamad; Firdaus Hayati; Nicholas Pang Tze Ping (2020)
Background Gastric trichobezoar happens when there is an indigestible substance or food found in the gastrointestinal tract. It is a rare presentation which is usually associated with trichotillomania and trichopagia. The presentation may not be specific and is usually related to dyspepsia-like symptoms. In the worst-case scenario, this may cause gastric outlet or intestinal obstruction which eventually requires surgery. Case presentation We present a 36-year-old lady with underlying end-stage renal failure (ESRF) and undiagnosed mental health issues who was treated for recurrent episodes of gastritis. Imaging modalities revealed intragastric foreign body ingestion which is consistent with gastric trichobezoar. She eventually underwent laparotomy and gastrotomy to remove the foreign body. Postoperatively, she was referred and followed-up by the psychiatric team. Conclusion Gastric trichobezoar has strong associations with psychiatric disorders. With the co-existence of an ESRF, uraemia might contribute to the aetiology of the trichotillomania and trichophagia. Open surgery is the choice of definitive management especially if bezoars are larger. Should the recurrence be remitted, a biopsychosocial modality and regular haemodialysis is the most sustainable approach to ensure the behaviour does not persist.